2013
DOI: 10.1080/10942912.2011.555900
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oven and Microwave Heating on the Total Antioxidant Capacity of Dietary Onions Grown in Turkey

Abstract: The active components of largely consumed dietary onions (Allium species) in Turkey were extracted with water and ethanol, separately heated in a drying oven (at 50 • C, for 1-4 h) and in a microwave oven (at 90 W, for 1-4 min), and their total antioxidant capacity was determined with different electron transfer-based assays. Five different onion species/aerial parts, namely yellow, red, white, fresh green leaf, and fresh green root, were measured for total antioxidant capacity with different methods, the hier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…[11,25] When comparing different studies, it is worth remembering that the effect of cooking likely depends on the vegetable structure, cooking procedures, extraction solvents, and antioxidant assays. [26] Our results revealed that the type of vegetables (fresh or frozen) should be taken into consideration.…”
Section: Discussionmentioning
confidence: 85%
“…[11,25] When comparing different studies, it is worth remembering that the effect of cooking likely depends on the vegetable structure, cooking procedures, extraction solvents, and antioxidant assays. [26] Our results revealed that the type of vegetables (fresh or frozen) should be taken into consideration.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, GC-MS was performed to analyze the volatile components of the ethyl acetate fraction, which showed the highest antioxidant activity in AGE. A total of 23 compounds (Table 1) Organosulfur compounds found in garlic have been shown to exert diverse biological effects such as antioxidant effects, anti-inflammatory properties, inhibition of platelet aggregation, reduction of systolic blood pressure, and reduction of cholesterol levels [17,18]. The spectrum of these sulfur-containing compounds depends considerably upon the methods of extraction of the original garlic bulbs, as well as upon the solvent conditions of processing [19].…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…The recent literature is rich in both in vivo and in vitro studies reporting the anti-thrombotic-, [1] hypolipidemic-, [2,3] anti-diabetic-, [4,5] anti-obesity-, [6] antioxidant-, [7][8][9] anti-inflammatory-, [10] cancer chemopreventive-, [11] and antiparasitic- [12,13] properties of onion extracts. Moreover, some epidemiological studies suggest that a diet rich in onions may have a favorable effect on the risk of acute myocardial infarction [14] and benign prostatic hyperplasia.…”
Section: Introductionmentioning
confidence: 99%